Children’s rights in Africa : an appraisal of the African Committee of Experts on the rights and welfare of the child - Teshome, Tilahun (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2007.